Ultrapermeable Nickel–Cobalt–Manganese/Alumina Inverse Opal as a Coke‐Tolerant and Pressure‐Drop‐Free Catalyst for the Dry Reforming of Methane. Issue 10 (15th March 2018) - Kim, Won Yong; Lee, Byung Jun; Park, Hunmin; Choi, Yo Han; Kim, Ju Hun; Lee, Jae Sung
Abstract: An inverse opal‐structured Ni‐Co‐Mn/Al2 O3 catalyst with ultrahigh permeability was prepared by a sol–gel method templated by poly(methyl methacrylate) opal‐structured nanospheres. This catalyst exhibited excellent coke tolerance and a negligible reactor pressure drop in the dry reforming of methane. The highly permeable, unique macroporous structure allowed facile mass transport, which not only reduced the amount of coke deposition but also enhanced coke tolerance. Therefore, invariant CO2 /CH4 conversions despite substantial coke formation were observed. Abstract : A dry run : An inverse opal‐structured Ni‐Co‐Mn/Al2 O3 catalyst with ultrahigh permeability exhibits excellent coke tolerance and a negligible reactor pressure drop in the dry reforming of methane. The highly permeable macroporous structure allows facile mass transport, which reduces coke deposition and enhances coke tolerance; thus, this catalyst exhibits invariant CO2 /CH4 conversions despite substantial coke formation.